Inventory Control and Price Theory - Whitin, T. M. (Management Science, 1955)
In spite of the high level of interest in inventory control that has sprung up recently among statisticians, economists, and businessmen, very little has been written that indicates the fundamental connection between price theory and inventory control. Most of the inventory control systems now in operation assume a given price structure. The analysis is frequently restricted to cost minimization. Economic theorists, on the other hand, have concerned themselves with profit maximization but have not ordinarily concerned themselves with the realistic details underlying the construction of their curves. Only in the event that other variables external to the cost minimization problem are assigned optimal values will the cost minimization problem be equivalent to profit maximization.